Settling the debate: does digitalisation impact the economic growth in the European Union Member States? - Oana-Ramona Lobonț; Cristina Criste; Ciel Bovary; Alexandra-Mădălina Țăran (Technological and Economic Development of Economy)
This research analyses the influence of digitalisation (Digitalisation Composite Indicator (ITC)) on economic growth (GDP per capita) by scrutinising the progression of digitalisation intensity and its impact. Digital technology has the potential to exert a substantial influence on various facets of the national economy, significantly impacting economic growth, innovation, and overall quality of life. Given the disparities among European Union Member States concerning governance quality, the imperative of digitalisation becomes evident in advancing economic prosperity, irrespective of a country’s development status. Specifically, our study aims to evaluate the effects of the implementation of digital tools on economic growth in the Member States of the European Union (EU-27) from 2017 to 2021. Two advanced methods, Principal Component Analysis (PCA) and the Ordinary Least Square model (OLS), were employed to conduct the empirical research. The findings indicate that before the pandemic, the level of digitalisation was subpar, marked by limited technological advancement. Nations exhibiting a heightened degree of digitalisation also demonstrate elevated levels of economic development. These results underscore countries’ need to realign and reconfigure their digital transformation strategies, emphasising incorporating digital technologies and cultivating ongoing innovation to bolster long-term economic growth.